Il Governo del Sistema Integrato Città-Trasporti-Energia Integrating Land Use, Transport and Energy Planning - Rocco Papa (Smart City, Urban Planning for a Sustainable Future, 2017)
heories about the origins and developments of modern cities seem to agree, without exception, to a point: the city is the place of maximum concentration of exchange. Activities, in fact, are located into urban and metropolitan agglomerations to minimize the resources needed to meet the growing need for relationships and exchanges with other activities. In recent years, the concentration and specialization of these activities have led to an extraordinary increase in intensity and quality of exchange needs, with the obvious consequence of congestion in most metropolitan areas with predictable consequences on the sustainability of urban areas, on the quality of life of its inhabitants and on the energy consumption associated with the growing demand for mobility. As a result, in recent years, several authors have argued for greater integration between urban planning policies, mobility management and energy efficiency. In this context, this volume aims to provide a contribution in this direction and presents the results of a research project aimed at the development of an integrated city-mobility-energy governance model. In particular, the first part of this work give an overview of the complex relationships between mobility, energy consumption and built environment through a meta-analysis of the recent literature. Specifically, in this section, the two main sources of energy consumption in urban areas (energy consumption in the residential sector and energy consumption of transport) are considered. These sectors represent, according to the latest estimates, respectively 32% and 35% of the final energy consumption. The section introduces several characteristics of the built environment such as density, functional mix or accessibility and described as such factors affect energy consumption in the transport and residential sectors. Understanding these relationships is of crucial importance for the development of a coordinated mix of actions aimed at reducing energy consumption in urban areas. Subsequently, the main models present in the literature for estimating residential energy consumption and urban transport energy consumption are presented, paying particular attention to the strengths and weaknesses of each model, the complexity and the related technical and operational aspects related to the implementation of such models. In the second part of this work, the focus is on the techniques for the representation and classification of energy consumption in urban areas through an application to the case study of Naples. Particularly, this section places particular emphasis on the new opportunities offered by the Geographic Information Systems (GIS) and by the increasing availability of new data sources. The work integrates the use of "traditional" data sources such as census surveys, new data sources (in particular open and large data) with spatial analyzes developed ad hoc to provide exhaustive knowledge of energy consumption patterns within the city of Naples. The proposed methodology is validated by comparing the results obtained with the previously available data for the study area and by the implementation of spatial statistical analyzes in a GIS environment. The proposed methodology is a useful tool for public decision-makers and policy makers aimed at defining integrated government strategies for the reducing and optimizing of public and private energy consumption. In particular, the methodology described in this work is useful for classifying and representing energy consumption on an urban scale, for the identification of critical areas in terms of consumption, and for ex post evaluation of interventions on the urban system.